Bulgaria : Third Review Under the Stand-By Arrangement and Request for Waiver of Applicability of Performance Criteria. (IMF Staff Country Reports; Country Report, 2003)
Bulgaria's macroeconomic performance, in the face of the prolonged slowdown in the EU, has been impressive, but further efforts are required. The government's fiscal policy has underpinned recent economic success, and pressures to loosen such policies should be resisted. Fiscal reforms have progressed, but momentum needs to be maintained for some time to come. Robust growth can be sustained over the medium term only with a revitalization of structural reforms. The rapid growth in credit to the private sector is welcome, but presents challenges.